Aqueous extract of Paullinia cupana attenuates renal and hematological effects associated with ketoprofen. Issue 1 (3rd December 2020) - Belló, Caroline; Prestes, Ana Paula; Schemberger, Josiane Aparecida; Hacke, Ana Carolina Mendes; Pereira, Romaiana Picada; Manente, Francine Alessandra; Carlos, Iracilda Zeppone; de Andrade, Cleverton Roberto; Fernandes, Daniel; da Cruz, Ivana Beatrice Manica; Unfer, Taís Cristina; Vellosa, José Carlos Rebuglio
Abstract: This study aimed to evaluate the effect of aqueous extract of Paullinia cupana (AEG) against ketoprofen side effects, through biochemical, hematological, and histological parameters. AEG showed antioxidant activity in the DPPH scavenging (IC50  = 17.00 ± 1.00 µg/ml) and HPLC analysis revealed that this extract is constituted by antioxidants (caffeine, catechins, theobromine, and polyphenols). In vivo experiments in female Wistar rats demonstrated that alterations in urea, creatinine, and uric acid levels promoted ( p  < .05) by ketoprofen were reversed when AEG was co‐administered. Ketoprofen significantly decreased the catalase levels of animal tissues ( p  < .05), which were restored when AEG was co‐administered with the mentioned drug. Histological analysis showed that AEG protected tissues from damages caused by ketoprofen. Moreover, AEG reestablished the number of white blood cells, which had decreased when ketoprofen was administered. In conclusion, this study suggested that the association between ketoprofen and AEG may be an alternative to reduce health damages caused by this drug. Practical applications: Paullinia cupana, popularly known as guaraná, is commonly consumed as a beverage in Brazil and exhibits pharmacological and beneficial effects to humans. Ketoprofen is an efficacious drug employed in the treatment of inflammatory processes. However, this drug can cause several side effects in humans. Thus, the usage of natural products and plant extracts that can reduce such undesirable effects consists in a valuable strategy to be applied in therapeutic interventions. Abstract : Aqueous extract from guarana (AEG) was constituted by antioxidant compounds. Combination between ketoprofen/AEG can reduce the side effects caused by this drug. AEG was able to prevent damage to catalase caused by ketoprofen.